2022
DOI: 10.1371/journal.pone.0268330
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of severe coronary microvascular dysfunction post-PCI in patients with STEMI: A systematic review and meta-analysis

Abstract: Coronary microvascular dysfunction (CMVD) is common and associated with poorer outcomes in patients with ST Segment Elevation Myocardial Infarction (STEMI). The index of microcirculatory resistance (IMR) and the index of hyperemic microvascular resistance (HMR) are both invasive indexes of microvascular resistance proposed for the diagnosis of severe CMVD after primary percutaneous coronary intervention (pPCI). However, these indexes are not routinely assessed in STEMI patients. Our main objective was to clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, another study suggested that the bimodal shape of the thermodilution curve, rather than the index of microvascular resistance value itself, indicated an increased risk of MACEs within six months, and this might be a result of capillary obstructions [ 76 ]. A systematic review of 1094 patients further suggested that the index of hyperemic microvascular resistance and the index of microcirculatory resistance in patients with STEMI after PCI aided in the early identification and early risk stratification of severe CMD and were prognostic indicators of MACEs [ 77 ]. In addition, CMD could be a prognostic indicator of MACEs in patients with hypertrophic cardiomyopathy, obesity, aortic stenosis, or chronic kidney disease [ 59 , 78 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study suggested that the bimodal shape of the thermodilution curve, rather than the index of microvascular resistance value itself, indicated an increased risk of MACEs within six months, and this might be a result of capillary obstructions [ 76 ]. A systematic review of 1094 patients further suggested that the index of hyperemic microvascular resistance and the index of microcirculatory resistance in patients with STEMI after PCI aided in the early identification and early risk stratification of severe CMD and were prognostic indicators of MACEs [ 77 ]. In addition, CMD could be a prognostic indicator of MACEs in patients with hypertrophic cardiomyopathy, obesity, aortic stenosis, or chronic kidney disease [ 59 , 78 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each methods has its own strengths and weaknesses [ 7 ]. Studies have shown that the index of microcirculatory resistance (IMR) and hyperemic microvascular resistance (HMR) are useful for the early identification of severe CMD in patients with STEMI after PCI, which are associated with a higher risk of long-term MACEs in patients with STEMI [ 14 ]. However, both IMR and HMR are invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Patients underwent follow-up for 13 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months. CMD was found to be an independent predictor of all 3).…”
Section: Clinical Follow-upmentioning
confidence: 99%
“…The endpoints were all‐cause death, nonfatal MI, and combined cardiovascular events with hospitalization for heart failure, and follow‐up ranged from 6 months to 7 years. Using an index of microcirculatory resistance (IMR) > 40 or hyperemic microvascular resistance (HMR) > 3 mmHg/cm/s as an indicator for severe CMVD, the results showed that severe CMVD had a worse prognosis, with an HR of 3.42 compared with nonsevere CMVD 16 . A meta‐analysis of 46 studies showed an incidence of MINOCA of 6% (patients’ median age 55 years), which was more common in young women without hyperlipidemia, and 12‐month all‐cause mortality was lower in patients with MINOCA than MIOCA (4.7% vs. 6.7%) 17 .…”
Section: Definition Clinical Classification and Epidemiology Of Cmvdmentioning
confidence: 99%